Genetic variation of carotenoids in Chinese bread wheat cultivars and the effect of the 1BL.1RS translocation - Wenshuang LI,Shengnan ZHAI,Hui JIN,Weie WEN,Jindong LIU,Xianchun XIA,Zhonghu HE (Frontiers of Agricultural Science and Engineering, 2016)
Carotenoid content of wheat is an important criterion for prediction of the commercial and nutritional value of products made from bread wheat (Triticum aestivum) cultivars. The objective of this study was to determine the major components of carotenoids in Chinese wheat using ultra performance liquid chromatography (UPLC) including lutein, zeaxanthin, α-carotene and β-carotene. Grain carotenoid content was investigated in 217 cultivars from three major Chinese wheat regions and from seven other countries grown in two environments. Genotype contributed to the majority of variation in carotenoid components. Lutein, zeaxanthin and β-carotene concentrations varied from 18.3 to 100.1, 4.9 to 12.0 and 0.9 to 48.7 μg per 100 g in wheat flour with an average of 40.2, 7.2 and 18.2 μg per 100 g, respectively. Lutein (61.3%) was the main carotenoid component, followed by β-carotene (27.7%) and zeaxanthin (11.0%). No α-carotene was detected. Total carotenoids, lutein, zeaxanthin and β-carotene were all higher in cultivars with the 1BL.1RS translocation compared to those without the translocation. This is the first report on assay of lutein, zeaxanthin and β-carotene concentrations for a large number of wheat cultivars. These data will be useful for genetic improvement of wheat carotenoid content and for understanding of the carotenoid biosynthetic pathway in wheat.